2012
DOI: 10.1038/nature10843
|View full text |Cite
|
Sign up to set email alerts
|

Strict evolutionary conservation followed rapid gene loss on human and rhesus Y chromosomes

Abstract: The human X and Y chromosomes evolved from an ordinary pair of autosomes during the past 200–300 million years1–3. Due to genetic decay, the human MSY (male-specific region of Y chromosome) retains only three percent of the ancestral autosomes’ genes4,5. This evolutionary decay was driven by a series of five “stratification” events. Each event suppressed X-Y crossing over within a chromosome segment or “stratum”, incorporated that segment into the MSY, and subjected its genes to the erosive forces that attend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
294
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 261 publications
(311 citation statements)
references
References 28 publications
12
294
2
3
Order By: Relevance
“…Regions targeted by our approach are frequently missing or grossly misassembled by whole-genome shotgun sequence assembly using either capillary or next-generation sequencing platforms (Alkan et al 2011b), still requiring highquality sequencing of large-insert clones to correctly resolve. Analysis of the mouse and human genomes suggests that these typically correspond to 300-500 regions (;140-150 Mbp) per genome, including in some cases almost entire chromosomes, such as the Y chromosome (Hughes et al 2012). The approach we have described provides a strategy to resolve these more structurally complex regions during the final stages of assembly, ensuring that the 1000-2000 genes mapping therein become incorporated within future mammalian genome assemblies (Alkan et al 2011b;Church et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regions targeted by our approach are frequently missing or grossly misassembled by whole-genome shotgun sequence assembly using either capillary or next-generation sequencing platforms (Alkan et al 2011b), still requiring highquality sequencing of large-insert clones to correctly resolve. Analysis of the mouse and human genomes suggests that these typically correspond to 300-500 regions (;140-150 Mbp) per genome, including in some cases almost entire chromosomes, such as the Y chromosome (Hughes et al 2012). The approach we have described provides a strategy to resolve these more structurally complex regions during the final stages of assembly, ensuring that the 1000-2000 genes mapping therein become incorporated within future mammalian genome assemblies (Alkan et al 2011b;Church et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Finishing of the human and mouse genomes involved selecting large-insert BAC clones and subjecting them to capillary-based shotgun sequence and assembly (English et al 2012). Sanger-based assembly of large-insert clones has been typically a time-consuming and expensive operation requiring the infrastructure of large genome sequencing centers and specialists focused on particular problematic or repetitive regions (Zody et al 2008;Dennis et al 2012;Hughes et al 2012). Such activities can significantly improve the quality of genomes, including the discovery of missing genes and gene families.…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%
“…From studies of mammals (6,7,11,56,57) and Drosophila (58-60), it is known that the Y chromosomes in both groups have lost most of their ancestral gene repertoires and have acquired copious amounts of repetitive and ampliconic/palindromic DNA. In the ∼250 My since Drosophila and Anopheles last shared a common Dipteran ancestor, there has been parallel evolution of heteromorphic sex chromosomes from the same ancestral linkage group (61), implying that the Anopheles Y must have undergone a similar fate of massive ancestral gene loss and genomic degradation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recently showed that even very small laboratory populations of phage with high mutation rates tend toward fitness plateaus. In addition, a recent comparison of human, chimpanzee, and rhesus Y chromosomes demonstrated that after an initial period of degradation following the halt of recombination, gene loss in the human Y chromosome effectively stopped (Hughes et al 2012). Finally, theoretical work by Loewe (2006) has revealed several "genomic decay paradoxes" (i.e., species that persist despite predicted unsustainable genomic decay), including human mitochondria.…”
mentioning
confidence: 99%